2011
DOI: 10.4097/kjae.2011.60.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative renal function in patients is unaltered after robotic-assisted radical prostatectomy

Abstract: BackgroundPneumoperitoneum with an intra-abdominal pressure (IAP) of 14 mmHg is known to decrease renal function. Robotic-assisted radical prostatectomy (RARP) requires an IAP of more than 15 mmHg for operation. Therefore, we retrospectively investigated whether patients who underwent RARP experienced renal insufficiency during the postoperative period (at postoperative days 7 and 30).MethodsOne hundred patients who underwent RARP were enrolled in this study. Preoperative serum blood urea nitrogen (BUN) and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…However, another study showed a completely opposite result; i.e., the incidence of AKI after RARP was significantly lower than that after ORP (5). In yet other studies, postoperative renal function was unaltered in patients who underwent RARP (3,6). These inconsistencies might be attributable to the diagnostic time of AKI or the timing of blood sampling, given that fewer patients who underwent RARP than ORP in our study met the AKI criteria on POD1 (<24 h after surgery).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, another study showed a completely opposite result; i.e., the incidence of AKI after RARP was significantly lower than that after ORP (5). In yet other studies, postoperative renal function was unaltered in patients who underwent RARP (3,6). These inconsistencies might be attributable to the diagnostic time of AKI or the timing of blood sampling, given that fewer patients who underwent RARP than ORP in our study met the AKI criteria on POD1 (<24 h after surgery).…”
Section: Discussionmentioning
confidence: 92%
“…To the contrary, another study reported that the incidence of AKI after RARP was significantly lower than that after ORP (5). Yet other studies reported that postoperative renal function was unaltered in patients who underwent RARP (3,6). Therefore, there is currently no consensus regarding the risk of AKI after RARP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have said that RALP does not lead to long - term postoperative renal dysfunction. However, in this study only RLAP patients were included in the study, so no comparison was made with the RRP method (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies on this issue have reported that postoperative renal function is unaltered after RALP, even under using a pressure of 20 mm Hg for pneumoperitoneum. 25 , 26 However, these earlier reports analyzed the change in the creatinine clearance or the value of eGFR to measure the differences between preoperative and postoperative renal function, instead of using validated criteria. Also, those studies analyzed only patients that underwent RALP, so the outcomes were not comparable to patients who underwent RRP.…”
Section: Discussionmentioning
confidence: 99%